Genetic association studies - Balding, David (Henry Stewart Talks, 2009)
Linkage vs. association, Common variants for common diseases, Genealogy, Linkage disequilibrium, Founder haplotypes, Genetic heterogeneity, Hardy Weinberg equilibrium, Principal component analysis, Single SNP tests of association for case-control data, Armitage trend test, Logistic regression, Quantitative traits, Bayesian analyses, Multiple testing, Haplotype-based analyses, Inferring phase, Problems with haplotype analyses, Imputation, Genetic association studies, Family-based tests of linkage and association, Software